Implementasi Algoritma Haversine Formula Pada Aplikasi Sadewa (Sistem Informasi Destinasi Wisata) Kota Salatiga Berbasis Android - Yusuf Ma'iin Rohmatulloh; Bambang Agus Herlambang; Setyoningsih Wibowo (STMIK Sinar Nusantara, 2022)
Abstract - Salatiga is a city in Central Java Province which is located in the middle of two big cities, namely Semarang City which are 49 km away and Surakarta City which is 52 km away. During the colonialism, the Dutch government dubbed Salatiga as